Case Report: Abnormally Low Glycosylated Hemoglobin A1c Caused by Clinically Silent Rare β-Thalassemia in a Tujia Chinese Woman - Gao, Wei; Jin, Yanwen; Wang, Minjin; Huang, Yan; Tang, Huairong (Frontiers in Endocrinology, 2022)
Background: Glycosylated hemoglobin A1c (HbA1c) is an important means of monitoring blood glucose and diagnosing diabetes. High-performance liquid chromatography (HPLC) is the most widely used method to detect HbA1c in clinical practice. However, the results of HbA1c by HPLC are susceptible to hemoglobinopathy. Here, we report a case of discordantly low HbA1c with an abnormal chromatogram caused by rare β-thalassemia. Case description: A 36-year-old Tujia Chinese woman presented with an abnormally low HbA1c level of 3.4% by HPLC in a health check-up. The chromatogram of HbA1c showed an abnormal peak. Fasting blood glucose, routine blood tests and serum bilirubin were normal. Her body mass index was 27.86 kg/m2. Hemoglobin electrophoresis showed low hemoglobin A and abnormal hemoglobin β-chain variants. The thalassemia gene test suggested a rare type of β-thalassemia (gene sequencing HBB: c.170G>A, Hb J-Bangkok (GGC->GAC at codon 56)in a beta heterozygous mutation). Glycated albumin (GA) was slightly increased. Oral glucose tolerance tests and insulin release tests indicated impaired glucose tolerance and insulin resistance. The hematologist advised follow-up visits. The endocrinologist recommended that the patient adopt lifestyle intervention. Three months later, GA returned to normal and impaired glucose tolerance, and insulin resistance improved. Conclusions: Clinically silent β-thalassemia may lead to low HbA1c values and abnormal chromatograms by HPLC. In these circumstances, differential diagnosis is important. Checking the chromatogram may be helpful in interpreting HbA1c as well as identifying hemoglobinopathy. Further tests, such as GA, OGTT, hemoglobin electrophoresis and genetic tests, are needed for differential diagnosis.